RRM2B-Mediated Regulation of Mitochondrial Activity and Inflammation under Oxidative Stress - Er-Chieh Cho; Mei-Ling Kuo; Jia-hui Cheng; Yu-Chi Cheng; Yi-Chen Hsieh; Yun-Ru Liu; Rong-Hong Hsieh; Yun Yen (Mediators of Inflammation)
RRM2B is a critical ribonucleotide reductase (RR) subunit that exists as p53-inducible and p53-dependent molecule. The p53-independent regulation of RRM2B has been recently studied, and FOXO3 was identified as a novel regulator of RRM2B. However, the p53-independent regulation of RRM2B, particularly under oxidative stress, remains largely unknown. In this study, we investigated the role of RRM2B underoxidative stress-induced DNA damage and further examined the regulation of mitochondrial and inflammatory genes by RRM2B. Our study is the first to report the critical role of RRM2B in mitochondrial homeostasis and the inflammation signaling pathway in a p53-independent manner. Furthermore, our study provides novel insights into the role of the RR in inflammatory diseases.